The price adjustment in a stock transfer contract - Ferrero Álvarez-Calderón, Guillermo (2023)
In this article, the authors highlight the importance of setting the price of shares as a preliminary step for transferring them in the context of corporate mergers and acquisitions.To this end, they analyze the different mechanisms available to the parties to make a price adjustment that makes the valuation reasonable, proportional, and durable. Finally, it is discussed which of these mechanisms is more convenient and efficient for the buyers and sellers, considering the particularities of each one of them.